Beyond discovery : moving academic research to the market - Schelhorn, Jean E.; Herbers, Joan M. (Oxford University Press USA, 2022)
Academic discoveries account for some of the most successful products in the marketplace, from pharmaceutical blockbusters like Lyricar to household names like GatoradeTM. Yet few researchers understand the process of technology transfer or the various pathways for commercialisation available to them. 'Beyond Discovery' is a guide for researchers interested in moving their inventions from the laboratory to the marketplace. Focusing particularly on scientists and engineers, the volume demystifies the process of commercialisation by offering clarity on key complex topics, including technology transfer, intellectual property, and the uneven landscape for inventors of different genders and ethnicities.